(untitled) (Global Journal of Human-Social Science, 2012)
The literature existing on entrepreneurship implicitly assumes that entrepreneurship and government and economic growth are positively related with each other and there is a positive correlation among them However few studies whether theoretical or empirical analyze such relation in an explicit manner This paper aims to study the entrepreneurship notion and the barriers of entrepreneurship and mainly the role of government in enhancing entrepreneurship in the society